Search for a scalar partner of the top quark in the jets plus missing transverse momentum final state at √s = 13 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2017)
A search for pair production of a scalar partner of the top quark in events with four or more jets plus missing transverse momentum is presented. An analysis of 36.1 fb-1 of √s = 13 TeV proton-proton collisions collected using the ATLAS detector at the LHC yields no significant excess over the expected Standard Model background. To interpret the results a simplified supersymmetric model is used where the top squark is assumed to decay via ~t1 → t(*) ~X01 and ~t1 → b~X±1 → bW(*) ~X01, where ~X01 (~X±1) denotes the lightest neutralino (chargino). Exclusion limits are placed in terms of the top-squark and neutralino masses. Assuming a branching ratio of 100% to t ~X01, top-squark masses in the range 450-1000 GeV are excluded for ~X01 masses below 160 GeV. In the case where m~t1 ~ mt +m~X01 , top-squark masses in the range 235-590 GeV are excluded.